JADID PHILOSOPHICAL REVIEWS (American Journal of Research in Humanities and Social Sciences, 2025)
The independence of our country has not been easily captured. As Hürrance sewed his life, our crucial ancestors, who had been arrogantly said in the pri'am, was killed in this direction. Similar views about the previous history Bishor finally during this time of the world today, we also contribute to the effectiveness of Murad in the sky of this bladder today.